Variable drivers of primary versus secondary nesting; density‐dependence and drought effects on greater sage‐grouse. (15th March 2017) - Blomberg, Erik J.; Gibson, Daniel; Atamian, Michael T.; Sedinger, James S.
Abstract : Organisms seek to maximize fitness by balancing reproductive allocations against mortality risk, given selection pressures inherent to the environment. However, environmental conditions are often dynamic and unpredictable, which complicates the ability to achieve such a balance, and may require reproductive adjustments depending on prevailing conditions. We evaluated the effects of density‐dependent, density‐independent (drought), and individual (age, body condition) factors on nesting decisions of female greater sage‐grouse in the American Great Basin. We obtained relocations and recorded reproductive histories from 287 radio‐marked females over a period of 10 yr, and applied these data to a multi‐state model that estimated probabilities of initiating a first nest (primary nesting rate) or a second nest, given loss of a first (secondary nesting rate). This approach allowed us to evaluate the relative association between nesting rates and covariates while accounting for imperfect detection of nests. Sage‐grouse primary and secondary nesting were influenced differently by density dependence and drought. Primary nesting was high and relatively constant among years despite variable drought conditions, but was negatively associated with population size (density dependence). Secondary nesting was lower and more variable compared to primary nesting, was similarly influenced by density‐dependence, and was also sensitive to drought conditions. Females known to initiate second nests were in better body condition than females that only initiated first nests, and females of intermediate age had higher primary nesting rates, whereas secondary nesting was unaffected by age. Our results suggest that females were more flexible and responded more readily to changing conditions when allocating resources to second nests. These results are consistent with patterns that have been demonstrated for female allocation to clutch size in this system, and suggest that when conditions are poor second nests reflect a tipping point where reproductive costs (increased mortality) outweigh benefits (offspring reproductive value).